Determinants of vascular impairment in type 1 diabetes-impact of sex and connexin 37 gene polymorphism: A cross-sectional study - Piťhová, Pavlína; Cichrová, Michaela; Kvapil, Milan; Hubáček, Jaroslav A; Dlouhá, Dana; Piťha, Jan (Cardiovascular diabetology, 2024)
BACKGROUND: The associations of risk factors with vascular impairment in type 1 diabetes patients seem more complex than that in type 2 diabetes patients. Therefore, we analyzed the associations between traditional and novel cardiovascular risk factors and vascular parameters in individuals with T1D and modifications of these associations according to sex and genetic factors. METHODS: In a cross-sectional study, we analyzed the association of risk factors in T1D individuals younger than 65 years using vascular parameters, such as ankle brachial index (ABI) and toe brachial index (TBI), duplex ultrasound, measuring the presence of plaques in carotid and femoral arteries (Belcaro score) and intima media thickness of carotid arteries (CIMT). We also used photoplethysmography, which measured the interbranch index expressed as the Oliva-Roztocil index (ORI), and analyzed renal parameters, such as urine albumin/creatinine ratio (uACR) and glomerular filtration rate (GFR). We evaluated these associations using multivariate regression analysis, including interactions with sex and the gene for connexin 37 (Cx37) polymorphism (rs1764391). RESULTS: In 235 men and 227 women (mean age 43.6 ± 13.6 years; mean duration of diabetes 22.1 ± 11.3 years), pulse pressure was strongly associated with unfavorable values of most of the vascular parameters under study (ABI, TBI, Belcaro scores, uACR and ORI), whereas plasma lipids, represented by remnant cholesterol (cholesterol - LDL-HDL cholesterol), the atherogenic index of plasma (log (triglycerides/HDL cholesterol) and Lp(a), were associated primarily with renal impairment (uACR, GFR and lipoprotein (a)). Plasma non-HDL cholesterol was not associated with any vascular parameter under study. In contrast to pulse pressure, the associations of lipid factors with kidney and vascular parameters were modified by sex and the Cx37 gene. CONCLUSION: In addition to known information, easily obtainable risk factor, such as pulse pressure, should be considered in individuals with T1D irrespective of sex and genetic background. The associations of plasma lipids with kidney function are complex and associated with sex and genetic factors. The decision of whether pulse pressure, remnant lipoproteins, Lp(a) and other determinants of vascular damage should become treatment targets in T1D should be based on the results of future clinical trials.
Keywords: dospělí; protein alfa 4 mezerového spoje; Female; Phenotype; Carotid Intima-Media Thickness; Heart Disease Risk Factors; Adult; Diabetic Angiopathies; ženské pohlaví; průřezové studie; Glomerular Filtration Rate; lidé; tlakový index kotník-paže; Ankle Brachial Index; genetická predispozice k nemoci; Photoplethysmography; Genetic Predisposition to Disease; intimomediální šíře tepenné stěny; fotopletysmografie; Middle Aged; Diabetes Mellitus, Type 1; Sex Factors; Cross-Sectional Studies; Male; sexuální faktory; polymorfismus genetický; diabetické angiopatie; lidé středního věku; Gap Junction alpha-4 Protein; fenotyp; mužské pohlaví; Polymorphism, Genetic; rizikové faktory kardiovaskulárních chorob; diabetes mellitus 1. typu; hodnoty glomerulární filtrace; Humans